Boosting Productivity: The Role of Discipline, Motivation, and Workplace Environment - Remetwa, Alberto Viyandika; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of work discipline, work motivation, and workplace environment on employee productivity at PT Guntner Indonesia. Design/Methodology/Approach – This study employs an explanatory quantitative research design. Data were collected through Likert-scale questionnaires distributed to 130 employees selected using simple random sampling. The data were analyzed using multiple linear regression with IBM SPSS version 27 after conducting instrument tests, classical assumption tests, and statistical hypothesis testing to examine the relationships among the variables. Findings – The results indicate that work discipline has a positive and significant effect on employee productivity. Work motivation also has a positive and significant effect on employee productivity. Furthermore, the workplace environment positively and significantly influences employee productivity. These findings demonstrate that improving employee discipline, strengthening work motivation, and creating a supportive workplace environment can enhance workforce productivity in manufacturing organizations.   Originality/Value This research is original in simultaneously examining work discipline, motivation, and workplace environment in a single empirical model. The findings provide practical value by offering evidence-based recommendations for improving productivity through human resource management practices.